Pectin Nanoparticle-Loaded Soft Coral Nephthea sp. Extract as In Situ Gel Enhances Chronic Wound Healing: In Vitro, In Vivo, and In Silico Studies - Nevine H. Hassan; Seham S. El-Hawary; Mahmoud Emam; Mohamed A. Rabeh; Mohamed A. Tantawy; Mohamed Seif; Radwa M. A. Abd-Elal; Gerhard Bringmann; Usama Ramadan Abdelmohsen; Nabil M. Selim (MDPI AG, 2023)
This study shed light for the first time on the in vivo diabetic wound healing potential activity of natural marine soft coral polymeric nanoparticle in situ gel using an excision wound model. A Nephthea sp. methanol-methylene chloride extract loaded with pectin nanoparticles (LPNs) was created. For the preparation of in situ gel, ion-gelation techniques, the entrapment efficiency, the particle size, the polydispersity index, the zeta potential, the in-vitro drug release, and a transmission electron microscope were used and the best formula was selected. Using (UPLC-Q/TOF-MS), 27 secondary metabolites responsible for extract biological activity were identified. Isolation and identification of arachidic acid, oleic acid, nervonic acid, and bis-(2-ethylhexyl)-phthalate (DEHP) of Nephthea sp. was firstly reported here using NMR and mass spectral analyses. Moreover, LPN in situ gel has the best effects on regulating the proinflammatory cytokines (NF-κB, TNF-α, IL-6, and IL-1β) that were detected on days 7 and 15. The results were confirmed with an in vitro enzymatic inhibitory effect of the extract against glycogen synthase kinase (GSK-3) and matrix metalloproteinase-1 (MMP-1), with IC50 values of 0.178 ± 0.009 and 0.258 ± 0.011 µg/mL, respectively. The molecular docking study showed a free binding energy of −9.6 kcal/mol for chabrolosteroid E, with the highest binding affinity for the enzyme (GSK-3), while isogosterone B had −7.8 kcal/mol for the enzyme (MMP-1). A pharmacokinetics study for chabrolohydroxybenzoquinone F and isogosterone B was performed, and it predicted the mode of action of wound healing activity.